Biomass-derived tube-like nitrogen and oxygen dual-doped porous carbon in the sulfur cathode for lithium sulfur battery. (August 2020) - Fan, Lanlan; Li, Zhenhuan; Kang, Weimin; Cheng, Bowen
Abstract: The high theoretical capacity around 1672 mA h g −1 and the energy density of 2567 Wh kg −1 and addition advantages of the low cost and environmental benignity, make lithium-sulfur batteries (LiSBs) next generation battery. However, due to restrictions on the low conductivity of sulfur and soluble polysulfides during discharge, electrochemical performance of the batteries is deteriorated. Heteroatom doped carbon as an effective strategy can improve the poor electrochemical performance caused by polysulfide shuttle. Hence, the nitrogen and oxygen dual-doped tube-like porous biomass-derived carbon from the fluffy catkins is successfully fabricated for the LiSBs. After carbonization and activation, the tube-like and unique mesoporous structure are obtained and maintained, and a high sulfur content of 82.5 wt% is achieved in tube-like activated carbon material/sulfur composites (TACM/S). The N, O dual-doping introduces more active sites and strong chemical adsorption to anchor the polysulfides, therefore remarkably ameliorating the intractable polysulfide shuttle effect and enhancing the utilization of sulfur. The electrochemical results show that the LiSBs with the TACM/S cathode exhibit high initial discharge capacities as high as 1041.7 mAh g −1 at 0.1 C, and outstanding capacity retention of about 77.5% after 500 cycles at 0.5 C with an ultralow capacity fading rate of 0.043% per cycle. Highlights: Tube-like porous biomass waste derived carbon has enough space to store sulfur. A high sulfur content of 82.5 wt%. Nitrogen and oxygen dual-doped ameliorating the terrible polysulfide shuttle effect.